The distal colon provides reserve storage capacity during colonic fluid overload. Issue 5 (1st November 1997) - Hammer, J; Pruckmayer, M; Bergmann, H; Kletter, K; Gangl, A
Abstract : Background —In addition to its absorptive function the capacity of the colon to retain fluid might be relevant in compensating for increased fluid loads and prevention of diarrhoea. The distal colon is considered to be mainly a conduit without extensive storage function. Aims —To evaluate colonic volume capacity in a model of pure osmotic diarrhoea. Methods —A non-absorbable, iso-osmotic solution (OS) containing polyethylene glycol (500 ml) was infused into the caecum of nine healthy volunteers; the control group (n=5) received an equal amount of an easily absorbable electrolyte solution (ES). Fluids were radiolabelled with technetium-99m and gamma camera images were obtained for 48 hours. Counts in the proximal and distal colon were measured and regional and overall colonic transit and stool output were quantified. Results —After OS, in contrast to ES, faecal output was increased significantly (p<0.05), but colonic transit after OS was not different from transit after ES (p>0.05). This indicates storage of OS in the colon: after OS infusion, counts in the proximal colon decreased linearly while the distal colon stored approximately 30% of radioactivity for the whole 48 hour study period. After OS, stool output correlated with distal (p<0.01), but not with proximal (p>0.05), colonic transit. In constrast, after ES, stool output was determined by proximal colonic transit (p<0.05) but not by transit through the distal colon (p>0.05). Conclusion —The distal colon retains non-absorbable fluid volumes extensively. In our model transit through the distal colon—but not the proximal colon—determined the time at which diarrhoea occurred.